علاقة ضغط العمل مع كفاءة الذات لدى ممرضي الإسعاف في مشفى تشرين الجامعي والمشفى الوطني في اللاذقية - اصبيره, ولاء (Latakia University Journal -Medical Sciences Series, 2018)
The aim of this study was to determine the relationship between job stress and self-efficacy of ambulance nurses in Tishreen university hospital and Al- Watany hospital in Lattakia. Whereas the sample consisted of 57 ambulance nurses from both hospitals (30 nurses from Tishreen university hospital, and 27ambulance nurse from Al- Watany hospital) Who were there during the period of data collection (convenience sample). The researcher used a tool of work stress levels used in the study of Al- Maany & Ajharshida (2006) and self-efficacy questionnaire used in the study of Abu Al-Husain (2010). The most important results were: The ambulance nurses in Tishreen university hospital and Al- Watany hospital suffering from intermediate level of work stress in general. While the level of self-efficiency of ambulance nurses in both hospitals was high. The results also confirmed that there were no statistically significant differences between work stress and self-efficiency of ambulance nurses in Tishreen university hospital and Al- Watany hospital in Lattakia. هدفت الدراسة إلى تحديد العلاقة بين ضغط العمل وكفاءة الذات لدى ممرضي الإسعاف في مشفى تشرين الجامعي والمشفى الوطني في اللاذقية. حيث تكونت العينة من 57 ممرض وممرضة من كلا المشفيين(30 ممرض وممرضة من مشفى تشرين الجامعي, و 27 ممرض وممرضة من المشفى الوطني) ممن تواجدوا أثناء فترة تجميع البيانات (العينة المتاحة). استخدمت الباحثة أداة تحديد ضغوط العمل ومستوياتها المستخدمة في دراسة المعاني و أخوارشيدة (2006) و استبيان كفاءة الذات المستخدم في دراسة أبو الحصين (2010). كان من أهم النتائج: أن ممرضي الإسعاف في مشفى تشرين الجامعي والمشفى الوطني يعانون من ضغوط عمل بمستوى متوسط بشكل عام. بينما كان مستوى كفاءة الذات لدى ممرضي الإسعاف في كلا المشفيين مرتفعاً. كما أكدت النتائج أنه لا توجد فروق ذات دلالة احصائية بين ضغوط العمل وكفاءة الذات لدى ممرضي الإسعاف في مشفى تشرين الجامعي والمشفى الوطني في اللاذقية.